Peran Orang Tua Meningkatkan Kecerdasan Emosional Anak; Analisis Faktor dan Strategi dalam Perspektif Islam - Chusnul Muali; Sulis Fatmawati (Prodi PAI STAI Sumatera Medan, 2022)
This study aims to analyze the role of parents in improving children's emotional intelligence with a focus on analyzing factors that increase emotional intelligence and strategies to increase emotional intelligence. This research was conducted in Alaspandan Village, Pakuniran District, Probolinggo. The research method used is qualitative, using a phenomenological approach—the source of data from research informants and library sources. The research informants consisted of two parents and children. At the same time, library sources comprised books, journals and research results. Data collection techniques using observation, interviews, and documentation studies. The study's results revealed that there were two influencing factors, namely internal and external. The research findings revealed that of the two, the internal factor became the most dominant factor, namely the family environment. The interactions and socialization that occur within the family have a dominant influence on the emotional development of children. The strategies used by parents to improve children's emotional intelligence are getting used to interacting with children, developing self-confidence, building child empathy, providing good role models, and controlling children's emotions.